AN IMPROVED BEM-LSM COUPLING-BASED TOPOLOGY OPTIMIZATION - Oliveira, Hugo Luiz; Leonel, Edson Denner (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
Topology Optimization (TO) is recognized as an important approach during early stages of structural concept. It allows the designer for finding higher performance solutions taking into account the limitation of natural resources. Most computational TO procedures are based on domain methods, in which feasible solutions are searched in relaxed design space. In such a case, jagged faces and grey-scale interpolations often lead to artificial stresses along the optimization. This study presents an algorithm for two-dimensional structural analysis, which overcomes such a difficulty. In addition it allows addressing both shape and topology changes. The coupling between Level Set Method and Boundary Element Method provides precise topologies along the whole optimization process. A benchmark example is used to illustrate its accuracy. The advantages of the proposed procedures are summarized as follows. Firstly, it is a gradient-based approach requiring information only at the boundary. Secondly, it leads to lower computational effort if compared to other available methodologies. The presented formulation shows efficiency and brings out new research perspectives.